2015
DOI: 10.1155/2015/310409
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice of Clinicians regarding Syndromic Management of Sexually Transmitted Infections in Public Health Facilities of Gamo Gofa Zone, South Ethiopia

Abstract: Background. Sexually Transmitted Infections (STIs) are the leading causes of morbidity among young adults. This study assessed the knowledge and practice of clinicians regarding syndromic management of STIs in public health facilities of Gamo Gofa Zone, Southern Ethiopia. Methods. Facility based cross-sectional study with mixed methods of data collection was conducted in public health facilities of Gamo Gofa Zone. The study included 250 clinicians and 12 health facilities, 26 mystery clients were hired, and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
1
6
1
Order By: Relevance
“…Although only 30% of physicians were aware of the guidelines for the syndromic management of STIs, clinically, the current study showed that the majority of physicians (76%) correctly prescribed the medication concerning the STIs' syndrome for their patients in the last 10 days. These findings go in line with the results of previous studies [10,11] that explained this finding by most physicians following their clinical flowchart in treating STI cases. However, our result is higher than the findings in these studies [11,16]; this might be because most participants had more than 10 years of experience with a high level of education.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although only 30% of physicians were aware of the guidelines for the syndromic management of STIs, clinically, the current study showed that the majority of physicians (76%) correctly prescribed the medication concerning the STIs' syndrome for their patients in the last 10 days. These findings go in line with the results of previous studies [10,11] that explained this finding by most physicians following their clinical flowchart in treating STI cases. However, our result is higher than the findings in these studies [11,16]; this might be because most participants had more than 10 years of experience with a high level of education.…”
Section: Discussionsupporting
confidence: 92%
“…PHC physicians are the cornerstone to implementing such an approach. However, different studies conducted in developing countries showed poor knowledge [10,11] and practice [12] among the health care workers regarding the syndromic management of STIs. Still, no data is known from Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study found 31% of providers post training prescribed the correct syndromic regimen to patient actors, however was more conservative in including errors in dose or frequency as well as drug name 25. In other countries with syndromic management, similar gaps in provider knowledge and practice have been identified,30 31 indicating a global need for interventions to support improved quality of STI care.…”
Section: Discussionmentioning
confidence: 99%
“…Only in 8.3% of cases did the clinicians follow the national guidelines correctly and treat the patient correctly using the SM approach. 19 Knowledge of SM of STIs was statistically lower (p = 0.005) among doctors who were more than 40 years of age (older doctors).…”
Section: Doctors' Knowledge Of the Sti Guidelinesmentioning
confidence: 90%
“…11 In a study done in South Ethiopia only in 8.3% of cases did the clinicians correctly adhere to the national SM guidelines for STIs; the majority used their experience to treat STI patients. 19 In a study conducted in six countries in West Africa, correct treatment was given to only 14.1% of patients according to the national syndromic STI management algorithms. 18 Many respondents (22 or 52.4%) made the diagnosis of STI syndromes using only history and physical examination of the patient according to the national syndromic STIs management guidelines.…”
Section: Adherence Practices To the Sti Guidelinesmentioning
confidence: 99%